Inovasi Problem Based Learning Berbasis Diferensiasi dan Digital pada Modul Bahasa Indonesia SMP (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the innovation of implementing Pembelajaran Berbasis Masalah integrated with differentiated instruction and digital technology in Indonesian language learning modules at the junior high school level. The research employed a qualitative descriptive approach. The research subjects were students of the Teacher Professional Education Program (PPG) in Indonesian Language and Literature who developed and implemented PBL-based Indonesian language learning modules. Data were collected through document analysis of the learning modules and semi-structured interviews with the PPG students as the module developers and implementers. The data were analyzed using content analysis techniques, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of PBL in Indonesian language modules fosters more contextual, meaningful, and student-centered learning. The integration of differentiated learning, Mengajar di Tingkat yang Tepat (TaRL), and Pengajaran Responsif Budaya (CRT) enables teachers to accommodate students’ diverse abilities and backgrounds. The use of digital media and social media platforms in assignments and presentations enhances students’ motivation, participation, and communication skills. Moreover, authentic assessment and reflective activities contribute to the development of students’ critical thinking, collaboration, and independence in line with the Pancasila Student Profile. Therefore, this PBL-based module can serve as a best practice model for innovative learning aligned with the Merdeka Curriculum and the demands of 21st-century education.